TECHNOLOGY OF MODERN TIMES AS A SOURCE OF THE “LEXICON OF COMMON FIGURATIVE UNITS” - Piirainen, Elisabeth (Proverbium - Yearbook, 2011)
The topic of this paper is widespread idioms (WIs) originating from the domain ‘modern technology’. These idioms are only a small part of the entire “Lexicon of Common Figurative Units” (i.e. the inventory of idioms which exist in a large number of European languages in a similar lexical structure and in the same figurative core meaning). The six idioms discussed here belong to one of the most recent layers of the common European figurative language.